MRI bullseye sign: An indicator of peripheral nerve constriction in parsonage‐turner syndrome. Issue 1 (2nd March 2017) - Sneag, Darryl B.; Saltzman, Eliana B.; Meister, David W.; Feinberg, Joseph H.; Lee, Steve K.; Wolfe, Scott W.
ABSTRACT: Introduction: The role of MRI in identifying hourglass constrictions (HGCs) of nerves in Parsonage‐Turner syndrome (PTS) is largely unknown. Methods: Six patients with PTS and absent or minimal recovery underwent MRI. Surgical exploration was performed at identified pathologic sites. Results: The time between symptom onset and surgery was 12.4 ± 6.9 months; the time between MRI and surgery was 1.3 ± 0.6 months. Involved nerves included suprascapular, axillary, radial, and median nerve anterior interosseous and pronator teres fascicles. Twenty‐three constriction sites in 10 nerves were identified on MRI. A "bullseye sign" of the nerve, identified immediately proximal to 21 of 23 sites, manifested as peripheral signal hyperintensity and central hypointensity orthogonal to the long axis of the nerve. All constrictions were confirmed operatively. Conclusions: In PTS, a bullseye sign on MRI can accurately localize HGCs, a previously unreported finding. Causes of HGCs and the bullseye sign are unknown. Muscle Nerve 56 : 99–106, 2017.